PENGARUH PENGGUNAAN METODE BERCERITA TERHADAP PENINGKATAN KEMAMPUAN MENYIMAK ANAK USIA DINI - Yuni Astiti, Ni Luh; Rasmini, Ni Wayan; Drajati Ekaningtyas, Ni Luh (Institut Agama Hindu Negeri Gde Pudja Mataram, 2021)
Early childhood has an exceptionally high creative mind power, so parental direction is required in associating in their lives, one of which is by utilizing the narrating technique. This examination utilizes a quantitative distinct technique with the kind of investigation. In this examination, see, audit and depict mathematically the item under investigation for what it's worth and reach determinations about it as indicated by the wonders that seemed when the exploration was directed through probes youth in the Pagutan Worms Climate. The technique for narrating in youth in the Pagutan worm climate is brought out through direct narrating with the media of picture story books. The expansion in listening capacity in youngsters can be seen from the information before the treatment (pre test) has a normal of 16.8 with an absolute score of 152 and after the treatment (post test) has a normal worth of 27.3 with an all out score of 246. So it tends to be seen an increment in the normal worth of 10.5. Hence the impact of utilizing the narrating strategy on youngsters' listening abilities is extremely sure.